Characterization and antibacterial activity of the nanocomposite of half-fin anchovy (Setipinna taty) hydrolysates/zinc oxide nanoparticles. (November 2017) - Song, Ru; Shi, Qingqing; Abdrabboh, Ghada Adel A.; Wei, Rongbian
Graphical abstract: Highlights: An antibacterial nanocomposite was prepared using a hydrothermal method. The ZnO NPs were functionalized with half-fin anchovy hydrolysates (HAHp). The nanocomposite of HAHp(3.0)/ZnO NPs caused disorganization in the cytomembrane. HAHp(3.0)/ZnO NPs induced the formation of ROS in intracellular cells. Abstract: Half-fin anchovy ( Setipinna taty ) hydrolysates (HAHp) was conjugated with zinc oxide nanoparticles (ZnO NPs) using a hydrothermal method to develop a novel antibacterial nanocomposite. The generated supernatants of the conjugate, designated as HAHp(3.0)/ZnO NPs, were characterized by transmission electron microscopy, high resolution transmission electron microscopy, and inductively coupled plasma-optical emission spectrometer. Results showed that HAHp(3.0) was absorbed on the surface of the ZnO NPs. The total content of zinc element was 9127.4 mg/kg in HAHp(3.0)/ZnO NPs. The increased antibacterial effects were observed for the HAHp(3.0)/ZnO NPs with the minimal inhibitory concentration of 3.5 μgprotein/mL against Escherichia coli ( E. coli ), Pseudomonas fluorescens, Salmonella and Staphylococcus aureus, compared to the bare HAHp(3.0). The antibacterial activity of HAHp(3.0)/ZnO NPs was further evaluated using E. coli as the model strain. The incubation of HAHp(3.0)/ZnO NPs increased the outer and inner membrane permeability in E. coli cells, and the leakages of potassium ions and the cytoplasmic β-galactosidase were detected during the process. Furthermore, porous structures were observed on the membrane of E. coli cells by scanning electron microscopy. In addition, the formation of intracellular reactive oxygen species was detected using fluorescence microscopy. The results suggested that the HAHp(3.0)/ZnO NPs could be a promising antibacterial nanocomposite.